Impact of connected conduit on pumping-induced seawater intrusion in a coastal karst aquifer - Wu, Xiujie; Xu, Zhongyuan; Xu, Zexuan; Hu, Bill X. (Frontiers in Marine Science, 2023)
Introduction Coastal karst aquifers face the risk of seawater intrusion due to groundwater development. Based on the conceptualization of Woodville Karst Plain (WKP), this study investigates the effect of karst conduit and pumping conditions on the aquifer vulnerability and pumping security. Methods According to the purposes of this study, two cases are considered: one with conduit and one without. Salinization levels are compared between two cases, considering pumping rates ranging from 50 to 200 m3/day and various pumping locations throughout the on-shore region. Results The results reveal that the aquifer with conduit is more susceptible to seawater intrusion at low pumping rates, whereas both scenarios experience significant salinization at high pumping rates. Specifically, in the non-conduit case, contamination is most prevalent when wells are located in the middle of the aquifer, while in the conduit case, pumping from inland areas poses high vulnerability. Moreover, conduit case and non-conduit case display different regions for pumping clean water. At low pumping rates, both cases show saline water being pumped from wells near the shore, and clean water is obtained from inland wells. At high pumping rates, the non-conduit case allows for clean water extraction from wells situated further inland, while in the conduit case, no wells within the entire aquifer are deemed safe. Discussion The analysis and findings of this study offer valuable insights for the management of groundwater in coastal karst aquifers, encompassing vulnerability assessment, selection of pumping locations, and determination of pumping rates.